Preparation of camellia oil-based W/O emulsions stabilized by tea polyphenol palmitate: Structuring camellia oil as a potential solid fat replacer. (15th March 2019) - Luo, Shui-Zhong; Hu, Xiang-Fang; Pan, Li-Hua; Zheng, Zhi; Zhao, Yan-Yan; Cao, Li-Li; Pang, Min; Hou, Zhi-Gang; Jiang, Shao-Tong
Highlights: Tea polyphenol palmitate particles effectively stabilize water-in-oil emulsions. Stable gel-like water-in-oil emulsions were fabricated and characterized. Solid camellia oil emulsions were prepared using tea polyphenol palmitate firstly. Water-in-oil emulsions with high slip melting point can be used as a solid fat replacer. Abstract: Water-in-oil (W/O) emulsions with a discontinuous aqueous phase dispersed in a continuous camellia oil phase were prepared by using tea polyphenol palmitate (Tp-palmitate) particle as effective stabilizers and their properties were characterized by droplet size, slip melting point (SMP), stability, microstructure and rheology. The d(4, 3) and d(3, 2) decreased from 7.96 μm to 4.67 μm and from 5.98 μm to 3.07 μm, respectively, and the SMP rose from 33.73 °C to 38.60 °C when the Tp-palmitate concentration increased from 1.0% to 2.5% (m/v). The storage stability, freeze/thaw stability and thermal stability significantly enhanced and the droplets aggregation progressively increased with the increasing of Tp-palmitate concentration. The liquid camellia oil was transformed into solid-like viscoelastic emulsion gels with a SMP of 38.6 °C when using 2.5% Tp-palmitate as particle stabilizers. This study provides a promising method for production of edible gel-like W/O emulsions using polyphenol-lipid complexes to potentially replace solid fats.